(untitled) (NAU Journal of Technology and Vocational Education, 2026)
Digital and future-skill integration in business education has emerged as a critical determinant of economic growth in knowledge economies. Yet, the extent to which business education programmes in developing sub-national contexts operationalize this integration remains inadequately documented. This study examined digital and future-skill integration in Business Education during the 2024/2025 academic session for Digital Economy Participation in Anambra State, Nigeria. Specifically, the study assessed the extent of digital literacy integration in Business Education curricula, examined the integration of future workplace skills in Business Education programmes, and analysed the level of institutional support for digital and future-skill integration. A descriptive survey research design was adopted. The population is 453 comprising 158 business education lecturers and 295 final-year business education students in tertiary institutions offering Business Education programmes in Anambra State. Using Taro Yamane’s formula, a sample size of 212 was determined. Stratified random sampling was employed in selecting the sample units. Data were collected using a structured questionnaire and analysed using mean and standard deviation, with a criterion mean of 2.50 on a four-point scale. The findings revealed that digital literacy integration in Business Education curricula is at a low extent (cluster M = 2.27), future workplace skills are integrated at a high extent (cluster M = 2.52), and institutional support for digital and future-skill integration is at a low extent (cluster M = 2.30). The study concluded that despite relative progress in embedding conventional future workplace competencies, foundational deficits in digital literacy integration and institutional support constrain graduates’ preparedness for digital economy participation in Anambra State. It was recommended, among others, that curriculum regulatory bodies mandate a comprehensive restructuring of Business Education curricula to embed digital literacy systematically, that institutions develop a structured future workplace skills framework addressing identified gaps in digital problem-solving, and that the state government establish a dedicated fund to strengthen digital infrastructure and faculty development in Business Education departments.